2000
DOI: 10.1099/00221287-146-5-1061
|View full text |Cite
|
Sign up to set email alerts
|

2-Oxoacid dehydrogenase multienzyme complexes in the halophilic Archaea? Gene sequences and protein structural predictions The GenBank accession number for the sequence reported in this paper is AF068743.

Abstract: All Archaea catalyse the conversion of pyruvate to acetyl-CoA via a simple pyruvate oxidoreductase. This is in contrast to the Eukarya and most aerobic bacteria, which use the pyruvate dehydrogenase multienzyme complex [PDHC], consisting of multiple copies of three component enzymes : E1 (pyruvate decarboxylase), E2 (lipoate acetyl-transferase) and E3 (dihydrolipoamide dehydrogenase, DHLipDH). Until now no PDHC activity has been found in the Archaea, although DHLipDH has been discovered in the extremely haloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
(31 reference statements)
1
30
1
Order By: Relevance
“…6 shows that the operon was highly expressed during growth on isoleucine, while no transcript could be detected when the cells were grown on pyruvate. As has been reported earlier (Jolley et al, 2000;van Ooyen & Soppa, 2007), the oadhc1 genes were transcribed into a single polycistronic transcript of about 5100 nt (data not shown), the size of which fits well with the combined size of the four genes (Fig. 1).…”
Section: Expression Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…6 shows that the operon was highly expressed during growth on isoleucine, while no transcript could be detected when the cells were grown on pyruvate. As has been reported earlier (Jolley et al, 2000;van Ooyen & Soppa, 2007), the oadhc1 genes were transcribed into a single polycistronic transcript of about 5100 nt (data not shown), the size of which fits well with the combined size of the four genes (Fig. 1).…”
Section: Expression Analysissupporting
confidence: 63%
“…More than 25 years ago it was discovered that in halophilic archaea the oxidative decarboxylation of pyruvate and 2-oxoglutarate under aerobic conditions is catalysed by 'anaerobic' OAFORs instead of 'aerobic' OADHCs, and thus OADHCs are not needed (Kerscher & Oesterhelt, 1981). Therefore, it was a surprise that four genes encoding an OADHC were discovered (Jolley et al, 1996(Jolley et al, , 2000. While Northern blot analysis showed that the genes are expressed, biochemical analyses as well as physiological characterization of a deletion mutant of the dihydrolipoamide dehydrogenase gene (e3, HVO_2961) indicated that none of the seven known OADHC substrates is used by this OADHC (Jolley et al, 1996; genes HVO_2958-HVO_2961 at www.halolex.mpg.de).…”
Section: Introductionmentioning
confidence: 99%
“…Another metabolic similarity between P. aerophilum and H. volcanii is the presence of genes with highly significant homology to 2-oxoacid dehydrogenase multienzyme complexes. 2-Oxoacid dehydrogenases are used in eukarya, and most aerobic bacteria to convert pyruvate to acetyl-CoA, whereas archaea are generally known to use a simple pyruvate oxidoreductase (47). An operon containing genes homologous to 2-oxoacid dehydrogenase enzymes: E1 (2-oxoacid decarboxylase), E2 (dihydrolipoamide acetyltransferase), and E3 (dihydrolipoamide dehydrogenase) has been characterized for H. volcanii; however, the enzymatic activity was not detected in the organism (47).…”
Section: ϫ23mentioning
confidence: 99%
“…2-Oxoacid dehydrogenases are used in eukarya, and most aerobic bacteria to convert pyruvate to acetyl-CoA, whereas archaea are generally known to use a simple pyruvate oxidoreductase (47). An operon containing genes homologous to 2-oxoacid dehydrogenase enzymes: E1 (2-oxoacid decarboxylase), E2 (dihydrolipoamide acetyltransferase), and E3 (dihydrolipoamide dehydrogenase) has been characterized for H. volcanii; however, the enzymatic activity was not detected in the organism (47). The P. aerophilum genome contains an apparent operon of not only the E1, E2, and E3 genes but also genes for lipoic acid synthetase and lipoate protein ligase B, known in eukarya and bacteria to act in the biosynthesis and attachment (to the E2 subunit) of lipoic acid cofactors (47).…”
Section: ϫ23mentioning
confidence: 99%
“…Neither 2-oxoacid nor acetoin dehydrogenase complex activity have ever been detected in any archaeon, although the presence of putative OADHC-encoding operons is evident from the genome sequences of a number of aerobic archaea, including species of the genera Halobacterium, Haloferax, Thermoplasma, Aeropyrum, Pyrobaculum and Sulfolobus [3][4][5]. To investigate the possible function of these archaeal genes, we have recombinantly expressed the four OADHC proteins from Thermoplasma acidophilum and shown them to assemble into an active branched-chain 2-oxoacid dehydrogenase complex of M r % 5 Â 10 6 that also possesses activity with pyruvate, albeit to a less extent [6].…”
Section: Introductionmentioning
confidence: 99%